A case report of uveitis with ocular hypertension - Konovalova, N. V.; Savko, V. V.; Khramenko, N. I.; Guzun, O. V.; Slobodianyk, S. B.; Zhuravok, Iu. A.; Savko, V. V. (Ukrainian Journal of Ophthalmology, 2025)
Based on a clinical case, we analyzed the characteristics of diagnosis, course, and treatment of uveitis in the presence of ocular hypertension.